Developing and evolution of industrial engineering and its paper in education (2016)
(Eng) Professionals with knowledge of industrial processes to ensure the best performance of the companies arisen in order to response to the needs of a society that constantly adapts and changes facing nature. This paper intended to show a vision of engineering through a literature review from its birth to what could be in its future; particularly the role of industrial engineering in education, based on articles from authors who have already researched and written on this subject, whose main conclusion is that the Industrial Engineering must be more participative regarding the institutionalism represented by universities, the company with its determining factor in society and the welfare of the population.